Ten Years' Follow-Up on Combined Palmar and Dorsal Internal Fixation of Complex Distal Radius Fractures. Issue 18 (May 2016) - Iselin, Lukas Daniel; Massy-Budmiger, Anne-Sophie; Droeser, Raoul A.; Mett, Tobias R.; Babst, Reto; Rikli, Daniel A.
Abstract : Abstract: Complex distal intra-articular radial fractures (AO Type C3) are rare, but are life-changing injuries. They are usually related to high-velocity trauma mechanisms in a working male population. We surveyed a cohort of these fractures treated in our institution to assess the functional long-term outcome. Twelve consecutive patients with comminuted intra-articular distal radial fractures were treated at our institution. Osteosynthesis was performed by a single senior surgeon with volar and dorsal extended approaches. The intermediate and final control included conventional X-ray, range of motion (ROM), grip strength, and the Disabilities of the Arm, Shoulder, and Hand index (DASH), as well as the Patient-rated Wrist Evaluation (PRWE) score for functional outcome at 1 and 10 years' of follow-up. At 10 years' follow-up, anatomic reconstruction with a step or gap of <1 mm was achieved in 10 of the 12 above-mentioned patients, whereas 2 patients were lost to follow-up. ROM was good to excellent in 8 patients. Median grip strength was 107% of the contralateral side. Median DASH-Index and PRWE were 2.3 and 6 respectively, at 10 years. Eight patients returned to premorbid heavy labor. One patient was retired at the time of injury. Combined volar and dorsal approaches allow achieving anatomical reconstruction in comminuted intra-articular distal radius fractures and reveal good functional outcomes at intermediate and long-time follow-up.